Entrepreneurial intention among foreign students in UUM: A case of Nigerian students - Auwalu, Ibrahim Najafi (2014)
Government all over the developing countries is doing enough to ensure that students now engage in entrepreneurship activities so as to reduce the level of unemployment among graduates. However, there is still lack of entrepreneurial intention among students. This study examined the entrepreneurial intention among foreign students in UUM. It was revealed that factors such as entrepreneurial orientation, entrepreneurial skill and enabling and supportive environment were key factors responsible for the lack of entrepreneurial intention among the students for building their entrepreneurial intention. In particular, the study examined the influence of entrepreneurial orientation, entrepreneurial skill and environmental factor on the entrepreneurial intention of the Nigerian students in UUM. Due to this, a cross-section study with quantitative questionnaire approach was conducted among Nigerian students in UUM. A convenient sampling technique was used to select 155 students who participated in the study through self-administered procedure. Overall, the result obtained shows that entrepreneurial skill and entrepreneurial orientations are significantly related to entrepreneurial intention while on the contrary; the result also shows that environmental factor was not significantly related to entrepreneurial intention. The implication of this study shows that Nigerian student in UUM have both entrepreneurial skill and entrepreneurial orientation to engage in entrepreneurial activities, as such the university assist them by providing an enabling and supportive environment that would enable the student to achieve their entrepreneurial intention in Malaysia. Finally, the theoretical and the practical aspects were clearly highlighted in addition to the limitation of the study and suggestion for future study.